2023
DOI: 10.1097/phm.0000000000002125
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Function and Rehabilitation Are as Important as Stroke Severity as Long-term Predictors of Cognitive Performance Post-stroke

Abstract: Objective: Although individuals with low stroke severity tend to recover well, cognitive impairment is common independent of stroke size or location. In this study, the patterns of recovery for individual cognitive domains and factors associated with outcome were examined. Design: A prospectively enrolled cohort of patients with minor stroke was administered cognitive testing at 1, 6, and 12 mos postinfarct. Composite T scores were generated for global cognition and well as independent cognitive domains at eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A previous study showed that cognitive function might be transiently impaired in patients with an acute stroke, and improved after rehabilitation. [36,37] Thus, the cognitive deficits might be a prominent feature in acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that cognitive function might be transiently impaired in patients with an acute stroke, and improved after rehabilitation. [36,37] Thus, the cognitive deficits might be a prominent feature in acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As the treatment of patients with large vessel occlusions has advanced over time resulting in smaller strokes and better long-term language and motor outcomes, cognitive impairment has been increasingly recognized as a significant factor that impacts overall function and quality of life. 2 Poststroke cognitive impairment represents a spectrum of phenotypes. It has been reported to occur in up to 60% to 70% of patients after a stroke.…”
Section: Heterogenous Disorder Complicates Classificationmentioning
confidence: 99%
“…Unfortunately, improvement can be short-lived, with up to half developing a recurrence of deficits leading to disability over the next 2 to 5 years. 2,3 Based on previous literature, it follows that the patterns of functional connectivity responsible for recovery are likely initially similar between groups but then diverge to result in varied long-term outcomes. 24 Further evidence, along with the ability to predict who is at greatest risk based on their connectivity profiles during early recovery, would allow not only for improved prognostication but also for the ability to potentially modify a patient’s trajectory based on a tangible therapeutic target.…”
Section: Treating Symptoms and Prognosticationmentioning
confidence: 99%
See 2 more Smart Citations